2016
DOI: 10.2139/ssrn.2781715
|View full text |Cite
|
Sign up to set email alerts
|

Which Updates During an Equity Crowdfunding Campaign Increase Crowd Participation?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
159
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(175 citation statements)
references
References 67 publications
10
159
2
4
Order By: Relevance
“…Besides quality signals, updates also play a role in the success of crowdfunding campaigns (Block et al. , Mollick , Xu et al. ).…”
Section: Communicating Work: Funding Transparency and Crowdfundingmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides quality signals, updates also play a role in the success of crowdfunding campaigns (Block et al. , Mollick , Xu et al. ).…”
Section: Communicating Work: Funding Transparency and Crowdfundingmentioning
confidence: 99%
“…Signals are powerful because they give information about the quality of the campaign to investors (donors). Besides quality signals, updates also play a role in the success of crowdfunding campaigns (Block et al 2018, Mollick 2014, Xu et al 2014). The argument is that updates generate more attention, visibility and excitement around a campaign (Kuppuswamy and Bayus 2018).…”
Section: Crowdfundingmentioning
confidence: 99%
“…Before we outline our hypotheses, it should be noted that whether a startup can build an enduring business generally depends on two factors. First, startups capable of sending effective signals (see Spence, ) to potential investors should receive more capital and, as a result, also have a lower probability of firm failure (see also Block, Hornuf, & Moritz, ). Second, regardless of whether firms can send effective signals, some firms might be inherently more valuable and thus have a lower probability of failure.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Mollick (2014) showed that including a video that presents the project and the quality of the pitch increase the chances of success. Hornuf and Schwienbacher (2018a) and Block et al (2018b) found that the updates posted by the entrepreneurs and comments posted by the crowd on the platform play a significant role in explaining the success of a campaign. Allison et al (2013) empirically validated these results regarding the rhetoric of the project presentation.…”
Section: Necessary Conditions For the Development Of Innovationmentioning
confidence: 99%